The Effect of Task Complexity, Time Budget Pressure and Machiavellian Traits on Auditor Dysfunctional Behavior With Work Stress Management as A Moderating Variable - Oktarina, Adelia; Muluk, Muhammad Adrian (Universitas Muhammadiyah Sorong, 2025)
This study aims to analyse the influence of task complexity, time budget pressure, and Machiavellian traits on dysfunctional auditor behaviour, This research incorporates job stress management as a moderating factor. A quantitative method was employed, using surveys distributed to auditors operating in public accounting firms within the South Jakarta region. The data were analyzed using the Structural Equation Modeling (SEM) technique with a Partial Least Squares (PLS) approach. The study’s findings demonstrate that task complexity, pressure from limited time budgets, and Machiavellian personality traits significantly and positively influence dysfunctional behavior among auditors. However, work stress management was not found to significantly moderate the relationship between task complexity, time budget pressure, or Machiavellian traits and auditors’ dysfunctional behaviour. These findings indicate that the influence of the three main factors on dysfunctional behaviour is not affected by the level of auditors' work stress management ability. This study is expected to serve as a basis for evaluation by organisations and auditors in understanding the causes of dysfunctional behaviour and the importance of systematically managing workloads.